2017
DOI: 10.1002/ajh.24928
|View full text |Cite
|
Sign up to set email alerts
|

Relatively favorable outcome after allogeneic stem cell transplantation for BCR‐ABL1‐positive AML: A survey from the acute leukemia working party of the European Society for blood and marrow transplantation (EBMT)

Abstract: The aim of the study was to assess the role of allogeneic stem cell transplantation (SCT) in patients diagnosed with BCR-ABL1-positive acute myeloid leukemia (AML). Fifty-seven patients (median age, 48 years, range: 19-67) with BCR-ABL1 positive AML undergoing SCT were identified. The majority of the patients (70%) received a TKI before the transplant. At SCT 48 patients were in CR (45 in CR1), while 9 patients were transplanted in a more advanced stage of the disease. MRD was negative (BCR-ABL1/ABL < 10 ) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…The CR rate of 75.9% and the deep molecular response rate as shown by RQ-PCR reflect the successful incorporation of a TKI into standard AML chemotherapy, which therefore can be used as bridging therapy to allogeneic HCT. Similar to our findings, a previous study also showed that pre-HCT MRD negativity was associated with a lower relapse rate and better survival [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The CR rate of 75.9% and the deep molecular response rate as shown by RQ-PCR reflect the successful incorporation of a TKI into standard AML chemotherapy, which therefore can be used as bridging therapy to allogeneic HCT. Similar to our findings, a previous study also showed that pre-HCT MRD negativity was associated with a lower relapse rate and better survival [18].…”
Section: Discussionsupporting
confidence: 92%
“…However, a recently published study that retrospectively analyzed the registry of the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation noted 18 patients treated with a TKI after HCT either as maintenance therapy or treatment for relapse. Hematologic relapse after allogeneic HCT occurred early, with a median interval of nearly 4 months post-HCT [18].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be related to the different MRD levels in each study. The rate of treatment with TKI before allo-HCT in our study was similar to that reported in a previous study [8] (77.8% and 70.5%, respectively). The MRD-negative status was previously noted in 12 of the 29 patients treated with TKI before allo-HCT and in only one of the six patients not treated with TKI [8].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the patients with BCR-ABL1 positive AML are often refractory to chemotherapy while the responses to imatinib are of limited duration [12]. A recent paper has reported that allogenic stem cell transplantation (allo-SCT) may improve outcome of younger patients [13]; however, given the small number of cases, the optimal therapy for AML with BCR-ABL1 has not been established yet. Beside common BCR-ABL1 transcripts, unusual transcripts have been also described in CML and acute leukemias.…”
Section: Discussionmentioning
confidence: 99%